Bacteriophage–derived double-stranded RNA (larifan) exerts variable effects on human blood monocytes depending on age and sex of donors - R. Dovhyi; M. Rudyk; T. Serhiichuk; Yu. Yumyna; A. Dvukhriadkina; K. Ostrovska; D. Pjanova; L. Skivka (The Ukrainian Biochemical Journal)
To date, great attention is paid to sex and age differences in the therapeutic effectiveness of drugs, including those that impact the immune system. Bacteriophage-derived dsRNA is the main component of the medicinal product Larifan, which exhibits interferonogenic activity. This study aimed to estimate the effect of Larifan on the activation status of human peripheral blood monocytes collected from donors of different ages and sex. Blood samples were obtained from the healthy volunteers, divided into 4 groups: young men and young women aged from 20 to 39 years, aged men and aged women from 54 to 69 years old. EDTA-anticoagulated blood samples were exposed to 200 μg/ml Larifan for 30 min, cells were washed and treated to study phagocytic index, ROS generation and expression of phenotypic markers. Only live monocytes selected by flow cytometry were included in the analysis. It was shown that monocytes from young as well as from aged females turned out to be quite inert to the treatment with Larifan. Monocytes from young males after the treatment demonstrated a minor decrease in phagocytic activity and significant down-regulation of ROS generation. Monocytes from aged adults showed clear sex-based differences in the basal cell phenotype. Thus, compared to monocytes from women, the monocytes from men over 50 after the treatment with Larifan showed decreased phagocytic activity and CD86 expression along with increased CD206 expression. Taken together, these results indicate the need for further studies of Larifan focused on developing personalized treatment depending on the age and sex of an individual.